Mini Percutaneous Nephrolithotomy in Ectopic Lumber Kidney: A Case Report - Hossain, Tohid Md Saiful; Islam, Sk Nazibul (Bangladesh Journal of Urology, 2023)
The chance of the development of hydronephrosis and the formation of stones is more in the ectopic kidney. Treatment of stones in ectopic kidneys is challenging for urologists due to abnormal location and rotation of the kidney and unfavourable local anatomy. We herein report a case of stone in a lumber kidney successfully managed by mini percutaneous nephrolithotomy (PCNL) in a prone position. A 55-year-old male presented with right lower abdominal pain. His CT scan of the KUB reveals the right kidney is in an ectopic location and has a hyperdense structure measuring about 15 mm in length, seen in the right renal pelvis with mild dilatation of the pelvicalyceal system. The patient underwent right-sided prone mini PCNL under the subarachnoid block (SAB), and complete stone clearance was achieved. There was no adverse event during or after surgery or post-operative blood transfusion. Bangladesh J. Urol. 2022; 25(2): 122-125